Age-related gait standards for healthy children and young people: the GOS-ICH paediatric gait centiles. Issue 8 (25th March 2019) - Alderson, Lucy M.; Joksaite, Sandra X; Kemp, Jennifer; Main, Eleanor; Watson, Tim; Platt, Frances M; Cortina-Borja, Mario
Abstract : Objective: To develop paediatric gait standards in healthy children and young people. Methods: This observational study aims to address the lack of population standards for gait measurements in children. Analysing gait in children affected by neurological or musculoskeletal conditions is an important component of paediatric assessment but is often confounded by developmental changes. The standards presented here do not require clinician expertise to interpret and offer an alternative to developmental tables of normalised gait data. Healthy children aged 1–19 years were recruited from community settings in London and Hertfordshire, UK. The GAITRite walkway was used to record measurements for each child for velocity, cadence, step length, base of support and stance, single and double support (as percentage of gait cycle). We fitted generalised linear additive models for location, scale and shape (gamlss). Results: We constructed percentile charts for seven gait variables measured on 624 (321 males) contemporary healthy children using a gamlss package in R. A clinical application of gait standards was explored. Conclusion: Age-related, gender-specific standards for seven gait variables were developed and are presented here. They have a familiar format and can be used clinically to aid diagnoses and to monitor change over time for both medical therapy and natural history of the condition. The clinical example demonstrates the potential of the Great Ormond Street Institute of Child Health Paediatric Gait Centiles to enable meaningful interpretation of change in an individual's performance and describes characteristic features of gait from a specific population throughout childhood.